Copular Clauses in Malay with Distal Demonstrative Itu - Mustaffa, Amir Rashad (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
The limited research in Malay nonverbal predication has predominantly revolved around the two attested copulas ialah and adalah. In fact, there is another grammatical element that appears to serve as a copula to the constituents flanking it, namely itu. Seeing that this distal demonstrative pronoun has never received any attention as a copula in the linguistics literature before, this study investigates the copular use of itu in Malay, focusing on its morphological, syntactic, semantic, and information-structural features within nonverbal clauses. Employing a qualitative approach through the descriptive method in linguistics, the analysis encompasses a range of nonverbal clauses taken from mainstream Malay news portals online to reveal that itu exhibits many copula-like characteristics. Constituent analysis was used to identify the linguistic features of the subject, the predicate, and most importantly itu. Only sentences with a generic subject and a predicate of the grammatical categories NP, AP, or PP were chosen so as to ensure that itu was not associated with the subject and the sentence was nonverbal. Morphologically, itu can combine with 3rd person ia to form a clarifying expression comparable to the embedded copular clause “which is…” in English. Syntactically, itu has the same distribution and behaviour as the other copulas in Malay. Semantically, itu is vacuous, making no contribution to the overall meaning of the clause. Information-structurally, itu does not carry any roles associated with the topic or focus. This research enriches our understanding of Malay linguistic structures, particularly in the underexplored area of nonverbal predication in Malay. Additionally, it provides historical linguists with insights into the evolution of pronominal elements into copulas as it happens. The findings have broader implications for the study of syntactic evolution and typological studies in Austronesian languages and beyond